2019
DOI: 10.18203/2394-6040.ijcmph20194495
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of gestational trophoblastic disease profile with special reference to mortality and pregnancy outcome after successful management of the same

Abstract: Background: Gestational trophoblastic disease (GTD) is a group of rare tumors that involve abnormal growth of cells inside a woman's uterus. GTD does not develop from cells of the uterus like cervical cancer or endometrial (uterine lining) cancer do. Instead, these tumors start in the cells that would normally develop into the placenta during pregnancy. GTD is unique because the maternal lesions arise from the fetal tissue as a molar pregnancy. All forms of GTD can be treated. In most cases the treatment produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…10 In one study, the highest cases of GTN patients were from the primigravida or nullipara group, comprising 115 (37.7%) patients out of 235 patients. 11 Meanwhile, Orr et al 12 considered that parity was not significantly related to GTN risk. Although in this study the parity status of GTN patients did not have enough data, 42% did not have data, other results showed that multiparous women were the dominant group, consisting of 14 (34%) patients compared to 24% nulliparous women.…”
Section: Resultsmentioning
confidence: 99%
“…10 In one study, the highest cases of GTN patients were from the primigravida or nullipara group, comprising 115 (37.7%) patients out of 235 patients. 11 Meanwhile, Orr et al 12 considered that parity was not significantly related to GTN risk. Although in this study the parity status of GTN patients did not have enough data, 42% did not have data, other results showed that multiparous women were the dominant group, consisting of 14 (34%) patients compared to 24% nulliparous women.…”
Section: Resultsmentioning
confidence: 99%